PENGGUNAAN GADGET ANDROID TERHADAP MORAL SISWA KELAS II SMP N 1 MAPAT TUNGGUL KABUPATEN PASAMAN - Nuraiman Nuraiman; Lena Puspa Deni (JURNAL MANAJEMEN PENDIDIKAN, 2022)
This research in the background by many of the moral declines that occurred in grade II students of SMP N 1 Mapat Tunggul in Pasaman Regency resulted from the use of Android Gadgets. This research aims to describe how android gadgets are used among grade II students of SMP N 1 Mapat Tunggul. To identify how the impact of the use of android gadgets on the morale of grade II students of SMP N 1 Mapat Tunggul and to find out how the efforts of schools, teachers and parents in limiting the use of android gadgets among grade II students of SMP N 1 Mapat Tunggul.